التفاعل الوراثي Xالبيئي وتحليل الثباتية لبعض الطرز الوراثية من القمح الطري (Triticum aestivum L.) في مواقع بيئية متباينة من الساحل السوري. - خوري, بولص; منصور, هبة (Latakia University Journal -Biological Sciences Series, 2018)
اختبر 11 طرازاً وراثياً من القمح الطري (Triticum aestivum L.) عبر ثلاثة مواقع بيئية مختلفة في الساحل السوري خلال موسم 2015- 2016 م تحت ظروف الزراعة المطرية بهدف تقييم هذه الطرز ودراسة التفاعل الوراثي X البيئي (GXE), وثباتية الغلة الحبية للطرز الوراثية المدروسة عبر هذه المواقع باستخدام 5 مؤشرات إحصائية للثباتية وهي:} X¯i, bi, S²d̅i تبعاً للعالمَين Eberhart and Russell (1966), معامل تباين الثباتية (s 2 i) تبعاً لـِ Wricke & Weber (1980), ودليل استقرار المكافئ البيئي ( (Wi تبعاً للعالمWricke (1962){ . تضمنت المادة الوراثية خمس سلالات مبشرة وستة أصناف محلية معتمدة تم الحصول عليها من المركز العربي لدراسات المناطق الجافة والأراضي القاحلة (ACSAD) والهيئة العامة للبحوث العلمية الزراعية (GCSAR), صممت التجربة في المواقع الثلاثة وفق تصميم القطاعات العشوائية الكاملة في ثلاثة مكررات, حللت البيانات إحصائياً وتمت المقارنة وفق اختبار أقل فرق معنوي عند مستوى دلالة 5%, حيث لوحظت فروق معنوية بين الطرز الوراثية بالنسبة لصفة الغلة الحبية (طن/هـ), وأظهر تحليل التباين التجميعي لصفة الغلة الحبية عبر البيئات وجود تباينات معنوية بين كلٍ من الطرز الوراثية, البيئات, وتفاعل طراز* بيئة, مما يشير إلى استجابات مختلفة للطرز الوراثية عبر البيئات المدروسة وفعالية تحليل الثباتية. أظهرت نتائج تحليل الثباتية تفوق الطرازَين الوراثيين (السلالة المبشرة أكساد 1147, والصنف دوما6) على جميع الطرز الوراثية المدروسة؛ حيث امتلكا ترتيباً متفوقاً في كل من متوسط الغلة الحبية عبر البيئات وثباتية في الغلة, وأبديا ملاءمةً مع جميع البيئات المختبَرة, مما يدل على أهمية استخدامهما في برامج تربية القمح المستقبلية للوصول إلى أصناف تجمع بين الغلة المتفوقة والثباتية العالية. Eleven genotypes of Bread Wheat (Triticum aestivum L.) were tested at three diverse locations in the Syrian Coast during the 2015-2016 season under rain-fed conditions to assess these genotypes and to study the Genotypes x Environments Interactions, and yield stability across environments using 5 statistical measures of stability:{ X¯i, bi, and S²d̅i according to Eberhart and Russell (1966), Stability Variance Index (s 2 i) according to Wricke and Weber (1980), Ecovalance Stability Index (Wi) according to Wricke (1962)}. Genetic material included 5 promising lines and 6 local varieties (provided by ACSAD and GCSAR).The experiment was designed using randomized complete block design with three replications, statistical data analysis was done, and least significant difference (L.S.D) test at 5% was applied for comparison of means. Significant differences were observed among bread wheat genotypes for grain yield (ton/ha), combined analysis of variance of grain yield across the three environments showed significant mean squares due to genotypes, environments and genotypes x environments interaction, suggesting differential responses of genotypes across studied environments and validity of stability analysis. Stability analysis for grain yield revealed that; the promising line ACSAD-1147 and Doma6 were more stable than other genotypes. Due to they had superior ranks for both average yield over environments and yield stability, which reveals the importance of these genotypes to reach varieties that combine relatively high yield and better stability in any future breeding programs.